A Study of the Stock Market’s Reaction to Announcements of Acquisitions by Mid Cap Indian IT Companies - K. S., Chetan (Indian Journal of Finance, 2012)
This paper analyses the stock market’s reactions to announcements of acquisitions in the Indian mid cap IT sector by using the event window method in the framework of the semi- strong form of efficient markets. This paper looks into the question - that does the stock market react irrationally to announcements of acquisitions in the mid cap IT sector, as result of which, there could be abnormal returns for the investors . Mid cap stocks are not efficiency priced all around the world, and a number of papers have supported this statement. The traditional notion of efficient markets described in the academic finance literature is quite strong ,and probably, is unrealistic. Irregularities may well exist in the market and even persist for periods of time, and the markets, at times, can be influenced by fads and fashions. For the present study, the researcher used a five-year period that is from 2005 to 2010 to select the sample for this study.